Refinement of ultrahigh aspect ratio pure aluminum through novel hydrostatic twist extrusion: microstructural and mechanical insights - E. Taherkhani; M.R. Sabour; A. Esmaeilnia; A. Jalali Aghchai; B. Straumal; G. Faraji (Journal of Materials Research and Technology)
Hydrostatic Twist Extrusion (HTE), a recently introduced Severe Plastic Deformation (SPD) technique, enables the refinement of pure aluminum billets with an ultrahigh aspect ratio, exceeding the limitations of conventional SPD methods. In this study, the microstructural and mechanical properties of HTE-processed aluminum were examined through Electron Backscatter Diffraction (EBSD), tensile testing, and hardness measurements. EBSD analysis revealed that HTE effectively reduced the grain size from approximately 99 μm–4.9 μm after two passes, with the formation of a lamellar structure. Additionally, the HTE process led to a considerable increase in the fraction of high-angle grain boundaries (HAGBs), with the HAGB fraction increasing from 33.4 % after the first pass to 56.7 % after the second pass. The application of high hydrostatic pressure during processing was key in accelerating the formation of HAGBs, contributing to enhanced microstructural properties. Following one pass, microhardness rose to around 43.7 HV, and further increased to 52.4 HV after two passes, from an initial 25.6 HV. Meanwhile, the total ductility loss was 14 % after the first pass and 10 % after the second. The results suggest that the strengthening mechanism in HTE-processed aluminum is primarily driven by grain boundary strengthening, dislocation interactions, and the beneficial effects of high hydrostatic pressure, which together enhance both strength and ductility. The study highlights the effectiveness of HTE in achieving a balanced combination of strength and ductility, making it a promising technique for the processing of ultrahigh aspect ratio pure aluminum.